Francisco Arceo de Fregenal and the treatment of clubfoot up to the sixteenth century - Vallejo, José Ramón (Array, 2018)
The correction of clubfoot as a subject of study is somewhat unusual, especially if one considers that up until the Renaissance only two authors dealt with the subject of this inherited disorder. On the one hand is Ambroise Pare, whose contributions to traumatology and orthopaedics are staggering, and on the other, Francisco Arceo de Fregenal, also known as the Ambroise Pare of Spain. Both men developed a method for treating this condition, and a special orthopaedic shoe. So, why is it that in the Spanish literature the French surgeon was considered the pioneer in the development of an orthopaedic boot from the start and not Arceo? Why was the work of the Spaniard not studied in depth, as it deserves to be? These questions troubled us and led us to write this paper, in which as the primary objective we decided to highlight Arceo’s contributions to the field of orthopaedics. Concrete arguments and works exist today that have led to common agreement among scholars of the subject that the Spanish surgeon was a Jewish convert. The social, economic and political conditions in Europe at that time may give us some idea of the difficulties for a Jewish convert in the sixteenth century, and clearly, it was difficult for a scientist to have followers who would defend his methods and technical ideas. Nevertheless, we believe that Francisco Arceo de Fregenal deserves more recognition and his work should continue to be studied in more depth.